Level Of Arabic Text Reading Skills In The Integrated Dini Curriculum - Zulkifli Din Mohamed Nasirudin; Harun Baharudin; Nik Mohd Rahimi Nik Yusoff; Nabihah Yusof (Ijaz Arabi Journal of Arabic Learning, 2022)
Reading skills are essential skills that need to be mastered in learning a foreign language. Thus, in line with 21st Century Education, this article aims to identify the level of mastery of Arabic text reading skills and inquiry practices among form two students in Government Aided Religious Schools. This article is a first phase study and a needs analysis study of three phases encompassed in the design and development research approach or called Design Development Research (DDR). The needs analysis phase was implemented using a survey study by distributing questionnaire instruments on 350 forms to two students from six Government Aided Religious Schools (SABK) in Melaka, Selangor, and Terengganu. Next, the data were analyzed using GNU PSPP 0.8.0 statistical software. To describe percentages, mean scores, and standard deviations. The study's findings found that the level of mastery of Arabic text reading skills among students showed a moderately high level with a mean of 3.69. However, based on the total mean of 8 items were at a high mean level, nine items were at a medium-high mean level, and three items were at a medium-low mean level. In conclusion, this study shows a need for developing a model of Arabic text reading skills based on inquiry activities to produce students who master the skills of Arabic text reading well.